2013
DOI: 10.5194/acp-13-6151-2013
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of biological aerosol particles and ice nuclei during and after rain

Abstract: Bioaerosols are relevant for public health and may play an important role in the climate system, but their atmospheric abundance, properties, and sources are not well understood. Here we show that the concentration of airborne biological particles in a North American forest ecosystem increases significantly during rain and that bioparticles are closely correlated with atmospheric ice nuclei (IN). The greatest increase of bioparticles and IN occurred in the size range of 2–6 μm, which is characteristic for bact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
301
5
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(355 citation statements)
references
References 86 publications
29
301
5
3
Order By: Relevance
“…Pollen is among the primary biological aerosol particles that nucleate ice (Hader et al, 2014). Its importance for precipitation on the regional scale has been suggested in a number of studies (Pöschl et al, 2010;Prenni et al, 2013;Huffman et al, 2013;Hader et al, 2014). Birch pollen is one of the most efficient pollen species at nucleating ice as high as 264 K (Diehl et al, 2001(Diehl et al, , 2002von Blohn et al, 2005;Pummer et al, 2012Augustin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pollen is among the primary biological aerosol particles that nucleate ice (Hader et al, 2014). Its importance for precipitation on the regional scale has been suggested in a number of studies (Pöschl et al, 2010;Prenni et al, 2013;Huffman et al, 2013;Hader et al, 2014). Birch pollen is one of the most efficient pollen species at nucleating ice as high as 264 K (Diehl et al, 2001(Diehl et al, , 2002von Blohn et al, 2005;Pummer et al, 2012Augustin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since some kinds of bioaerosols can act as ice nuclei even at temperatures warm than -10°C (Schnell and Vali, 1972;Diehl et al, 2001;Iannone et al, 2011;Knopf et al, 2011;Morris et al, 2013;Joly et al, 2014), bioaerosols as an important component of aerosols in the atmosphere have been paid much more attentions over the past decades (Schnell and Vali, 1972;Diehl et al, 2001;Iannone et al, 2011;Knopf et al, 2011;Morris et al, 2013). Ice nucleation-active bioaerosols have widely been found in different regions and climates (Schnell and Vali, 1976;Christner et al, 2008a;Christner et al, 2008b;Pratt et al, 2009;Conen et al, 2011;Garcia et al, 2012;Burrows et al, 2013;Huffman et al, 2013;Monteil et al, 2014;O'Sullivan et al, 2014). Recent numerical studies show that ice nucleation-active bioaerosols can trigger the ice multiplication in the warmbased precipitating shallow cumulus clouds (Ariya et al, 2009;Sun et al, 2010;Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…8), it is reasonable to suggest that those particles were perhaps ASOP. Also, numerous studies have reported enhancement of fluorescent particles after rain events [25][26][27][28] . Large super-micrometre fluorescent particles are commonly attributed to biogenic spores, bacteria, fungi, and so on.…”
mentioning
confidence: 99%